Role of intrapleural instillation of MESNA in the management of pleural adhesions - Amany Omar; Abd-Elazim Abo Elfadl; Yousef Ahmed; Hussein Elkhayat; Montaser Gamal (Egyptian Journal of Chest Disease and Tuberculosis, 2022)
Context Intrapleural adhesions and pleural fluid loculation is a common clinical problem. Several options are available to manage the intrapleural adhesions. MESNA has recently been used as a fibrinolytic agent and due to its efficacy and safety it is an option in treating intrapleural adhesions instead of other intrapleural fibrinolytics. Aims To assess the efficacy and safety of MESNA as a fibrinolytic agent in the management of loculated pleural effusions. Settings and design A prospective case series study at the Chest Department, Assiut University Hospital from October 2017 to March 2020. Patients and methods A prospective case series study has been conducted on 25 patients, who were admitted at the Chest Department, Assiut University Hospital. Patients presented with complex septated pleural effusion and their symptoms were anticipated to improve by pleural fluid drainage . MESNA was given daily for 3 consecutive days at a dose of 1800 mg diluted with 20 ml of normal saline and injected into the pleural cavity through the chest tube. The amount of drained fluid, chest ultrasound, and chest radiograph were used to evaluate the improvement of patients, assess the safety of MESNA, and detect any adverse effects. Results After installation of MESNA there is an increase in the amount of the fluid drained through the intercostal tube with significant difference before and after installation of MESNA (P<0.001) with a success rate of 64% in the studied patients. Conclusions Intrapleural installation of MESNA is a safe and effective therapy in the treatment of loculated plural effusions.